Problematika Penyeragaman Pemidanaan Tindak Pidana Korupsi Pada Peraturan Mahkamah Agung Nomor 1 Tahun 2020 Dalam Kaitannya Dengan Konsep Divine Justice Di Indonesia - Alam, Faris Satria; Juaningsih, Imas Novita (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
This study reviews the problems regarding the mechanism for convicting corruption cases in Supreme Court Regulation Number 1 of 2020 concerning Guidelines for Conviction of Article 2 and Article 3 of the Law on the Eradication of Corruption Crimes. The presence of these normative rules has created a de-organization of the freedom of judges which should still reflect and go high the conception of Divine Justice in accordance with the irah-irah which reads